Empowerment of women and mental health improvement with a Preventive approach - Shahin Shooshtari; M R Abedi; M Bahrami; Rahele Samouei (Journal of Education and Health Promotion, 2018)
Aim and Background: Mental health and empowerment are two of the women's essential needs. These two related concepts play an important role in women's lives. Therefore, this study aimed to investigate empowerment of women and its relation with mental health problem prevention during difficult situations. Methods: This qualitative study was conducted through semi-structured interviews with 33 experts in the fields of psychology, social sciences, women studies, medicine and crisis management specialists using snowball sampling in cities of Tehran, Isfahan, Tabriz, and Mashhad during the year 1395 (March 2016–March 2017). Samples were selected heterogeneously. The interview transcripts and codes were presented to the participants, and structural analysis was used for data evaluation. Results: The factors related to empowerment of women with consideration to their mental health were determined based on Longew theory and interviews and include: welfare (primary needs (biological and security) and developmental needs (social needs and dignity), access (facilities and values), knowledge (about inequalities and rights), participation (in politics, decision-making and society), and control (implementation and institutionalization of the above-mentioned needs). Conclusions: The indicators determined in this study show that empowerment has an important role in determining women's real position in society. Since women make up half of the population and affect society as a whole, the advantages of empowerment of women will be felt in the entire society.